The Library Environment, Aspects of Interior Planning. Proceedings of the Library Equipment Institute (St. Louis, Missouri, June 26-27, 1964) - American Library Association, Chicago, IL.; Poole, Frazer G.; American Library Association, Chicago, IL. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1965)
The texts of the papers given at the Library Equipment Institute, as well as the presentations of the panelists and the discussions between members of the audience and the program speakers, are included. Diagrams and other illustrative materials accompany the text. Specific topics include--(1) furnishings, (2) illumination, (3) audio, (4) transportation, and (5) flooring. (RK)
Sponsoring Agency: American Library Association, Chicago, IL. Library Administration Div.
Microfiche.
Keywords: Acoustical Environment; Lighting; Environment; Library Equipment; Library Facilities; Library Planning